Zootaxa 20 years: Phylum Porifera - Hooper, John N.a.; Wörheide, Gert; Hajdu, Eduardo; Erpenbeck, Dirk; de Voogd, Nicole J.; Klautau, Michelle (Zootaxa, 2021)
The peer-reviewed journal Zootaxa has accelerated the rate of sponge (Porifera) species discoveries in 289 peer-reviewed papers published between 2002 up until the end of 2020, describing 725 new species, six new subspecies, 27 new genera, four new subgenera, and 123 new species and genus names needed to resolve existing homonyms. Zootaxa has been the most prolific of all taxonomic journals in its contributions to describing new taxa of Porifera in modern times. This present article analyses these taxonomic contributions over the past 20 years of Zootaxa, including their trends and highlights pertaining to sponge publications.